The quadratic function g(x) = -3x^2 + 2x - 5 is expressed in standard form as g(x) = -3x^2 + 2x - 5, where a = -3, b = 2, and c = -5.
The quadratic function g(x) = -3x^2 + 2x - 5 is not in standard form, which is ax^2 + bx + c, where a, b, and c are constants. To express g(x) in standard form, we rearrange the terms:
g(x) = -3x^2 + 2x - 5
Combining like terms, we get:
g(x) = -3x^2 + 2x - 5
To express this in standard form, we reorder the terms by descending powers of x:
g(x) = -3x^2 + 2x - 5
Thus, the standard form of the quadratic function is g(x) = -3x^2 + 2x - 5, where a = -3, b = 2, and c = -5.
The question probable may be:
Consider the quadratic function g(x) = -3x^2 + 2x - 5. Express this quadratic function in standard form.